Advances of artificial intelligence in a green energy environment - Vasant, Pandian 1961-; Thomas, J. Joshua 1973-; Munapo, Elias; Weber, Gerhard-Wilhelm 1960- (Elsevier, AP, Academic Press, 2022)
Advances of Artificial Intelligence in a Green Energy Environment reviews the new technologies in intelligent computing and AI that are reducing the dimension of data coverage worldwide. This handbook describes intelligent optimization algorithms that can be applied in various branches of energy engineering where uncertainty is a major concern. Including AI methodologies and applying advanced evolutionary algorithms to real-world application problems for everyday life applications, this book considers distributed energy systems, hybrid renewable energy systems using AI methods, and new opportunities in blockchain technology in smart energy.Covering state-of-the-art developments in a fast-moving technology, this reference is useful for engineering students and researchers interested and working in the AI industry.- Looks at new techniques in artificial intelligence (AI) reducing the dimension of data coverage worldwide- Chapters include AI methodologies using enhanced hybrid swarm-based optimization algorithms- Includes flowchart diagrams for exampling optimizing techniques